Clerical Fascism or Presentism? - Trizuljak, Samuel (Dějiny – teorie – kritika, 2020)
The aim of this contribution is to show that the use of the heuristic construct of ‘clerical fascism’ increases the risks of presentism, that is, an interpretation systematically distorted due to the historian’s own worldview or views which are currently prevalent in general. The author traces these risks with respect to the description of the activities of the Catholic priest Ladislav Hanus during the early years of the wartime Slovak Republic, offered by Miloslav Szabó’s book Klérofašisti [Clerical Fascists]. The author shows how the use of the construct of ‘clerical fascism’ contributes to a distorted interpretation due to selective work with sources, neglect of some other relevant materials, and how it leads to dismissal of some important features of contemporary internal policy and results in a stylistically suggestive narrative. This distortion is most apparent in Szabó’s interpretation of Hanus’ key speech from November 1941. While Szabó sees it as the pinnacle of naive efforts to have the interests of the Catholic Church guaranteed by the Nazi Third Reich, the author explains that, to the contrary, Hanus’ speech likely represented an important intervention in the contemporary public debates and that his intervention sought to limit the growing influence of Nazi ideology in Slovakia. The author also points out that the risk of distorted interpretation is inherent in the very construct of the heuristic tool of ‘clerical fascism’, which arguably brings in doubt the interpretative approach applied in Szabó’s book as a whole. To eliminate the risks of presentism, the author recommends the methodology of intellectual history and a greater attention to the historiography of Catholic ‘modernism’.